1979
DOI: 10.1088/0022-3727/12/10/009
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic instability of a liquid sheet sprayed with an air stream

Abstract: The instability of a thin sheet of liquid moving in the same direction as an air stream is studied theoretically. It is found that instability occurs if the Weber number is less than a critical value related to the ratio of the air and liquid stream velocities. Also, the wavelength for maximum instability is found to be inversely proportional to this critical value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…(1) If fluids are inviscid, that is, = 0, it is reduced to dispersion relation as obtained by El-Sayed [15]. (2) In the absence of electric field and viscosity, (24) will represent the same dispersion relation as obtained by Rashed et al [9]. (3) In the limit when , , and tend to zero, (24) is reduced to dispersion relation as obtained by Squire [4].…”
Section: Normal Mode Analysis and Dispersion Relationmentioning
confidence: 82%
See 1 more Smart Citation
“…(1) If fluids are inviscid, that is, = 0, it is reduced to dispersion relation as obtained by El-Sayed [15]. (2) In the absence of electric field and viscosity, (24) will represent the same dispersion relation as obtained by Rashed et al [9]. (3) In the limit when , , and tend to zero, (24) is reduced to dispersion relation as obtained by Squire [4].…”
Section: Normal Mode Analysis and Dispersion Relationmentioning
confidence: 82%
“…Joostan et al [8] have studied the effect of capillary waves on a free and viscous liquid sheet. Rashed et al [9] have studied the disintegration of the liquid sheet according to perforated sheet mode and found that instability occurs if the Weber number is less than a critical value related to the ratio of the air and liquid stream velocities.…”
Section: Introductionmentioning
confidence: 99%
“…30 In the field of aerosol sciences, studies that might be relevant to enhancing the dispersion of CBW agents began in the late 1970s, mainly in collaboration with Egyptian scientists. 31 All in all, the scientific activities taking place in Saudi Arabia indicate the existence of an adequate technical and scientific domestic infrastructure, a beneficial interface between that infrastructure and foreign scientists, and the accumulation of fragmentary technical and scientific knowledge that may be instrumental in developing CBW capabilities. It follows that the technical and scientific resources observed in Saudi Arabia are probably sufficient to absorb whatever complementary foreign assistance might still be needed for local developmentand production of CBW.…”
Section: Scientific and Technical Infrastructurementioning
confidence: 99%